Thailand Social Monitor : Poverty and Public Policy - World Bank (Washington, DC, 2013)
This is the sixth issue of the "Thailand Social Monitor." It is written for Thai policymakers, to provide them with the best evidence currently available on poverty and public policy, and to strengthen the foundation for anti-poverty strategies in Thailand. This report approaches Poverty in Thailand from four perspectives: 1) the changing profile of the poor, who they are, where they live, their defining characteristics, so as to better understand the dimensions of the problem (Chapters 1 and 2); 2) the changing profile of income inequality in Thailand, to assess whether income distribution should be an issue for public policy (Chapters 3 and 4); 3) some of the strategic, cross-sectoral issues that are at the center of public policy debates on poverty reduction in Thailand (Chapter 4); and 4) the performance of recent policies and programs to reduce poverty, so as to appreciate the strengths and limitations of public policy in this challenging domain (Chapters 5 and 6). The coverage of this report is thus broad. However, while chapters 5 and 6 analyze targeted poverty interventions, they do not capture the full range of public efforts to reduce poverty, nor do they address the anti-poverty benefits of universal programs, such as education, health, transport, or agricultural services. Also, macroeconomic policies are not covered.